ANALISIS KESULITAN BELAJAR MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAIYAH PADA PEMBELAJARAN PAI - Nurjanah, Nurjanah; Saprin, Saprin; Rosdiana, Rosdiana; Rivai, Immawati (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to determine the form of learning difficulties and the factors that cause learning difficulties for PGMI B students class 2017 in PAI learning courses at the Tarbiyah and Teacher Training Faculty of UIN Alauddin Makassar. This research is a type of qualitative descriptive research using a pedagogic and sociological approach. The research was conducted at the Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar with the research subject being ten students of PGMI B class of 2017. The data collection method used in this study is by conducting observations, interviews, and documentation. The results showed that the forms of learning difficulties experienced by PGMI B students class 2017 Faculty of Tarbiyah and Teacher Training UIN Alauddin Makassar in PAI Learning courses were difficulties in understanding PAI learning materials, difficulties in remembering the material being taught and the learning methods used were monotonous. There are two factors that cause learning difficulties, namely internal and external factors. Internal factors consist of disturbed health conditions or physical disorders, low interest in learning, and lack of motivation to learn, while external factors for students are influenced by the learning environment at the university, the learning methods used are less varied, and the conditions of the study rooms are not comfortable.